ANALYSIS FROM THE STATURE RECOVERY OF OBESE INDIVIDUALS AND NON - OBESE AFTER A DAILY TASK. (Fiep Bulletin - online, 2014)
The mechanical of the intervertebral discs have for objective dissipate loads and is related with the reduction and increase of stature from the individuals during the day. Some studies have demonstrated that overloads change the capacity of the intervertebral discs to dissipate loads. This study aim to compare the recuperation of stature among individuals obese and non-obese to identify if the fat engages this mechanic property of the intervertebral discs. For this, 20 male individuals, 10 obese (BMI>30) and 10 non-obese (BMI
Keywords: Obesity; Intervertebral Disc; Back Pain.